Agricultural Unmanned Systems: Empowering Agriculture with Automation (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Automation is crucial for the advancement of modern agriculture. It has a significant role in enhancing production efficiency and output, reducing labor costs, addressing natural disasters, and boosting sustainability. Automation utilizes big data and artificial intelligence to monitor agricultural production. It introduces new farming models that adapt to the challenges of scalability and environmental changes, achieving precise and efficient agricultural development. This Special Issue, titled “Agricultural Unmanned Systems: Empowering Agriculture with Automation”, focuses on sharing knowledge related to integrated and precise operational agriculture systems in the sky, air, land, and water. It explores intelligent sensing and control technologies in smart agricultural unmanned systems to advance the progress of unmanned agriculture. Establishing global demonstration sites is essential. These sites support the revolutionary advancement of smart agricultural machinery in automated, intelligent, unmanned, cluster operations.